Family Support for Adolescent Girls and Young Women Living With HIV in Zambia: Benefits, Challenges, and Recommendations for Intervention Development. (15th March 2021) - Roberts, Sarah T.; Edwards, Patrick; Mulenga, Drosin; Chelwa, Nachela; Nyblade, Laura; Brander, Caila; Musheke, Maurice; Mbizvo, Michael; Subramanian, Sujha
Abstract: Lack of family involvement is barrier to antiretroviral therapy adherence among adolescent girls and young women (AGYW). This study assessed family support for AGYW's engagement along the HIV care continuum to inform the design of a family-focused intervention in Lusaka, Zambia. We conducted 16 in-depth interviews and four focus group discussions with 40 AGYW living with HIV. Three strategies were identified to strengthen family support. First, emotional and instrumental support are highly valued by AGYW and should be further developed or reinforced . Second, AGYW wanted more informational support and open discussion of HIV from family, and an intervention should aim to enhance these types of support. Third, existing appraisal support reinforced anticipated stigma among AGYW and discouraged disclosure, yet participants wished for more interactions with peers living with HIV. Appraisal support should therefore be reframed to help AGYW decide to whom they should disclose and how to do so safely.